Workshop on writing, evaluating and fine-tuning application for FRGS and PRGS Grants - Norhanani, Mohamad Nor (Penerbit UMP, 2015)
The research Office of Research and Innovation Department conducted a workshop on writing, evaluating and fine-tuning application for FRGS grants for the year 2015 at Legend Resort, Cherating in Pahang on April 20, 2015.